In(PO3)3 stabilised fluoroindate glasses - Messaddeq, Younes [UNESP]; Grando, D. [UNESP]; Melnikov, P. [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Oliveira, L. F C (Elsevier, 1998)
Results on thermal and optical characterization of new lanthanide containing fluoroindate glasses in the system InF3-BaF2-In(PO3)3 are presented. Good optical quality and very stable glasses presenting up to 5 mm in thickness could be prepared in this system. Thermal analysis, Raman scattering and Eu3+ luminescence were the techniques utilized. A novel method for In(PO3)3 synthesis is proposed and the dependence of physical properties and structural features on the polyphosphate content is stressed. © 1998 Elsevier Science S.A.
Keywords: Europium; Fluoride glasses; Indium polyphosphate; Composition effects; Fluorine compounds; Indium compounds; Luminescence of solids; Optical properties; Raman scattering; Synthesis (chemical); Thermoanalysis; Thermodynamic stability; Fluoroindate glass; Glass